Slag removal and accurate slag control method for continuous hot galvanizing automobile outer plate production
By fixing the aluminum content and iron content before maintenance of the zinc pot, combining cooling and slag removal and precise control of zinc liquid components, the Fe saturation solubility curve is drawn and linearized, the problem of zinc slag and small black spot defects is solved, and a high-quality surface of the automobile outer panel is achieved.
Patent Information
- Application Number
- CN202411634870.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-07
AI Technical Summary
The prior art is difficult to effectively remove zinc slag defects and small black spot defects, resulting in the surface quality of automobile outer panels being unable to meet high-grade requirements.
By fixing the aluminum content before maintenance of the zinc pot and saturating the iron content, combining cooling and slag removal and precise control of the zinc liquid components, the Fe saturation solubility curve is drawn and linearized, the Fe content in the zinc liquid can be accurately controlled.
Effectively reduce zinc slag and small black spot defects, improve the surface quality of galvanized products, and meet the needs of high-grade surface quality.
Smart Images

Figure CN119571237A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of automobile outer panels, and in particular to a slag removal and precise slag control method for continuous hot-dip galvanized automobile outer panel production. Background Art
[0002] One of the main factors affecting the exterior panels of automobiles is zinc slag defects, which include zinc slag defects in larger areas and small black spot defects (micro zinc slag) on the surface, such as Figure 1 and 2 Domestic and foreign research has found that zinc slag, especially zinc slag that causes surface defects, is mainly Fe 2 Al 5 Zn x At present, various steel companies have formed a variety of control methods, one of which is to use the Fe-Al-Zn ternary isotherm diagram to carry out slag making and deslagging.
[0003] Before the overhaul, the Al content in the zinc liquid is increased, and the temperature is lowered and the slag is removed during the overhaul, resulting in a certain window period of unsaturated Fe content. Then, the production of automobile outer panels is started, and the aluminum content is gradually reduced to keep the zinc liquid composition below the Fe saturation dissolution curve, thereby achieving the purpose of reducing zinc slag. The theoretical method is shown as follows: Figure 3 .
[0004] This theory has not been converted into a specific operating method. The aluminum reduction rate used is an estimated value based on experience. In addition, the equipment, raw materials, and production methods of each enterprise are different, so the rate of increase of the Fe content in the zinc liquid varies greatly. Blindly using the estimated value can easily cause the slag control method to fail and fail to achieve the purpose of slag removal and iron reduction. Therefore, a specific operating method is urgently needed to achieve slag removal and precise slag control. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a slag removal and precise slag control method for the production of continuous hot-dip galvanized automobile outer panels, so as to achieve the purpose of slag removal and iron reduction, and control the small black spot defects on the surface of the strip steel plate to meet the requirements of high-grade surface quality.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for removing slag and accurately controlling slag in the production of continuous hot-dip galvanized automobile outer panels. The Al content of the zinc pot is fixed before overhaul, and the iron content in the zinc pot is saturated. During overhaul, the temperature is lowered to remove slag and after standing, the Al reduction rate is controlled to produce outer panels.
[0008] Furthermore, in addition to cooling and slag removal, the actual temperature of the zinc pot during the entire production measurement and production process is T (unit: °C), and the target temperature of the zinc pot is T 0 (Unit: °C), T 0 -1≤T≤T0 +1.
[0009] Furthermore, during the production process, the Al content in the zinc pot is increased to 0.26-0.27% (unit: wt%), and then the added zinc ingot composition is controlled to reduce the Al content in the zinc liquid, and the Fe saturation content in the zinc liquid under the corresponding Al content is measured. When the Al content in the zinc pot is reduced to 0.15%, the measurement is terminated, and the Al and Fe contents in the zinc pot are recorded and the Fe saturation solubility curve is drawn. According to the Al content, it is divided into three sections: 0.18-0.21%, 0.21-0.24%, and 0.24-0.27%, and the curve is partitioned and linearized according to each section.
[0010] Furthermore, during the process of reducing Al in zinc liquid, the Al content is measured with 0.01% as the scale to correspond to the Fe content. The zinc liquid required for the measurement must not contain slag particles to ensure that the composition of the liquid zinc liquid is measured.
[0011] Furthermore, the Al content at each scale, the Fe content of the zinc pot is measured twice, the measurement interval time is not less than 24 hours, the measurement interval time is not less than 24 hours, the difference of the measured Fe content is less than 0.0003% (unit: wt%, if the condition is not met, the operation is repeated until the condition is met), at this time the Fe content in the zinc liquid has reached saturation (because Fe is continuously dissolved in the production process, the Fe content in the zinc liquid is considered to have reached saturation if it does not change), record and calculate the average value of the two measurements.
[0012] Furthermore, after the zinc pot is cooled and the slag is removed and left to stand, the time required from the start of production until the Fe in the zinc liquid reaches saturation is measured, and the Fe dissolution rate of the strip during the production process is calculated.
[0013] Furthermore, by using three inspections, the aluminum content is controlled within a certain value (excluding the boundaries) within the three intervals of 0.18-0.21%, 0.21-0.24%, and 0.24-0.27% before stopping, and the data X is recorded. 0 , X 1 , X 2 (Unit: wt%), using the above Fe saturation solubility curve, query X 0 , X 1 , X 2 The corresponding saturated Fe content Y under the composition 0 , Y 1 , Y 2 (Unit: wt%).
[0014] Further, the zinc pot is cooled to 435°C-440°C and maintained at this temperature for at least 24 hours, during which the slag is removed several times. 0 , X 1 , X2 , respectively, after cooling and removing slag, the Fe content in the zinc liquid was measured as M 0 、M 1 、M 2 (Unit: wt%).
[0015] Furthermore, after starting the machine, arrange the outer plate production, control the Al content in the zinc liquid, and control the addition of zinc ingots to keep the Al content in the zinc liquid X 0 , X 1 , X 2 After the start of production, measure the iron content in the zinc solution every 4 hours until the Fe content in the zinc solution reaches the saturation value Y 0 , Y 1 , Y 2 , record the time t 0 ,t 1 ,t 2 (Unit: hours).
[0016] Further, using the above data, the rate of Fe dissolution is calculated as V 0 、V 1 、V 2 (Unit: wt% / hour),V 0 =(Y 0 -M 0 ) / t 0 、V 1 =(Y 1 -M 1 ) / t 1 、V 2 =(Y 2 -M 2 ) / t 2 .
[0017] Furthermore, according to the method for removing slag and accurately controlling slag in the production of continuous hot-dip galvanized automobile outer panels according to claim 8, it is characterized in that by referring to the saturated solubility curve of Fe (iron), the corresponding saturated Fe content N is accurately found when the Al (aluminum) content is 0.18wt%, 0.21wt%, 0.24wt%, and 0.27wt%. 0 、N 1 、N 2 、N 3 , thus, the zinc liquid is clearly divided into four specific composition points. Next, the difference in Fe content between two adjacent composition points is calculated to obtain the absolute value |N 1 →N 0 ∣、∣N 2 →N 1 ∣、∣N 3 →N 2 ∣;
[0018] Further, the time t required for transition from one component point to the adjacent component point is calculated based on the above-mentioned calculated Fe dissolution rate. x ,t y ,t z , N 1 →N 0 、N 2 →N 1 、N 3 →N 2 , the time required t x ,t y ,t z , t x =|N 1 -N 0 ∣ / V 0 ,t y =|N 2 -N 1 ∣ / V 1 ,t z =|N 3 -N 2 ∣ / V 2 . Where V 0 、V 1 、V 2 Represents the Fe dissolution rate at different stages.
[0019] Furthermore, when the Al content is 0.18-0.21%, 0.21-0.24%, 0.24-0.27% (including the left boundary, excluding the right boundary), the Al reduction rate in the zinc liquid during production is V x 、V y 、V z , V x =(0.21%-0.18%) / t x 、V y =(0.24%-0.21%) / t y 、V z =(0.27%-0.24%) / t z .
[0020] Furthermore, in the process of producing the outer plate, the zinc ingot component is added to ensure that the Al reduction rate is in accordance with the corresponding aluminum content using the above V x 、V y 、V z The Al and Fe contents in the zinc solution are always kept below the linearized Fe saturation solubility curve. The smaller the Al content grouping interval, the closer the linearized curve is to the true value and the more accurate the data is.
[0021] Beneficial effects of the present invention:
[0022] The invention discloses a method for removing slag and accurately controlling slag in the production of continuous hot-dip galvanized automobile outer panels. Before the zinc pot is overhauled, the Al content is increased to 0.26%-0.27%, and then the zinc ingot component is controlled to be added during production to achieve Al reduction in zinc liquid, from which the Fe content in the saturated state is measured, the Fe saturation solubility curve is drawn, and the segmented linearization is performed; the zinc pot is cooled and deslaged by overhaul to change the Fe content in the zinc liquid, and the Fe content in the zinc liquid when unsaturated is measured. During production, the zinc ingot component is controlled to be added to indirectly control the Al content of the zinc liquid to remain unchanged, and the Fe content is saturated, so as to measure the Fe increase rate in the zinc liquid during the production of the outer panel; the Fe saturation solubility curve at a certain temperature is measured and segmented linearized, and the Fe increase rate of the zinc liquid is measured during the production of the outer panel. In order to ensure that the Al and Fe components in the zinc liquid are always below the Fe saturation solubility curve, the corresponding Al reduction rate is calculated. In the production of the outer panel, the zinc ingot component is controlled to be added to achieve the Al reduction rate according to the calculated value, thereby achieving accurate slag control.
[0023] The method of the present invention is practical and effective, and can effectively and accurately control zinc slag and micro zinc slag defects in small black spots, thereby improving the surface quality of galvanized products. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a physical picture of small black spots (micro zinc slag);
[0025] Figure 2 This is a micrograph of small black dots (micro zinc slag);
[0026] Figure 3 It is the Fe-Al-Zn isotherm at 460℃ and the trend chart of Fe and Al contents in zinc liquid;
[0027] Figure 4 Perform image matching and linearization for the data in Table 1;
[0028] Figure 5 Perform image matching and linearization on the data in Table 6. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0030] Example 1
[0031] Production line A mainly produces wide strip steel (small zinc pot), the zinc pot temperature is controlled at 455-457℃, and then 5% wt aluminum ingot is added to make the Al content in the zinc pot reach 0.27%, keep the aluminum content unchanged, take liquid from the zinc pot, and remove zinc slag with the liquid taker. Use fluorescence instrument for detection, the Fe content is 0.0065% for the first time and 0.0063% for the second time. Then Al is reduced by 0.01%, and the Fe content of the zinc pot is measured twice at each Al content of the scale. The measurement interval is not less than 24 hours, and the difference of the measured Fe content is less than 0.0003% (unit: wt%, if the condition is not met, repeat the operation until the condition is met), record and calculate the average value, the data is shown in Table 1.
[0032] Table 1
[0033]
[0034] Perform image matching and linearization on the data in the table, such as Figure 4 .
[0035] Before the three overhauls, the aluminum content was controlled at 0.20%, 0.22%, and 0.25% respectively before stopping. According to the Fe saturation solubility curve, the Fe content was found to be 0.0114%, 0.01%, and 0.0077% respectively. Then the zinc pot was cooled to 435℃, the temperature was maintained for 25 hours, and the slag was removed several times. The Fe content in the zinc pot was measured to be 0.0084%, 0.0072%, and 0.0057%. Then the temperature was raised to prepare for the production of outer plates. The production sequence of outer plates is as follows: 1.5mm 60-80 tons, 1.2mm 60-80 tons, 1.0mm 150-200 tons, 0.8mm 200-300 tons, 0.75mm 200-300 tons, 0.7mm 200-300 tons, and the average width is 1400-1500mm. The Fe content in the zinc solution was measured every 4 hours until the saturated Fe content was reached at the corresponding Al content, and the Fe increase rate was calculated, see Table 2.
[0036] Table 2
[0037]
[0038] When the Al content is 0.18%, 0.21%, 0.24%, and 0.27%, the corresponding saturated Fe content N 0 、N 1 、N 2 、N 3 , see Table 3.
[0039] Table 3
[0040] Al content (wt%) 0.18 0.21 0.24 0.27 Saturated Fe content (wt%) <![CDATA[0.0131(N 0 )]]> <![CDATA[0.0102(N 1 )]]> <![CDATA[0.0084(N 2 )]]> <![CDATA[0.0065(N 3 )]]>
[0041] According to the Fe dissolution rate calculated in Table 3 above, the Fe content is calculated from N 1 →N 0 、N 2 →N 1 、N 3 →N 2 Time required x ,t y ,t z Then, according to the formula, the Al reduction rate in the zinc solution required for production is V x 、V y 、V z , see Table 4.
[0042] Table 4
[0043] Al content range (wt%) Time taken (hours) Corresponding rate of aluminum reduction (wt% / hour) 0.18%-0.21% <![CDATA[11.6(t x )]]> <![CDATA[0.0026(V x )]]> 0.21%-0.24% <![CDATA[7.8(t y )]]> <![CDATA[0.0038(V y )]]> 0.24%-0.27% <![CDATA[11.2(t z )]]> <![CDATA[0.0027(V z )]]>
[0044] After the fourth cooling and slag removal of the zinc pot, the Al content of the zinc liquid was detected to be 0.265wt%. First, about 5 tons of zinc liquid were extracted, and then the outer plate was produced in the planned order. The thickness specifications were 1.5mm 65 tons, 1.2mm 79 tons, 1.0mm 156 tons, 0.8mm 274 tons, 0.75mm 292 tons, 0.7mm 257 tons, and the average width was 1470mm. Then, pure zinc ingots and zinc ingots with 0.15wt% Al content were added to reduce aluminum. When the Al content in the zinc liquid was between 0.24% and 0.27% (including the left boundary), the aluminum content was reduced according to 0.0027 (V z )wt% / hour, when the AL content of zinc liquid is between 0.21% and 0.24% (including the left boundary), the temperature is adjusted according to 0.0038 (V z )wt% / hour, when the AL content of zinc liquid is between 0.18% and 0.21% (including the left boundary), the temperature is adjusted according to 0.0026 (V z )wt% / hour. The final Al content of zinc liquid is 0.20% to end the outer plate production. The outer plate zinc slag produced by this production method meets the "05" grade requirements of DIN1623-2009 standard with a pass rate of 94.3%, and the number of small black spots is greatly reduced, as shown in Table 5.
[0045] Statistical explanation of the implementation example of small black spots: for the same specification of outer plates, 5 10cm*10cm square samples are taken from the edge and the middle of the strip, and the number of black spots on the front and back sides of the 10 samples is recorded, and the sum of the number of black spots on both sides of a single piece is calculated.
[0046] Table 5
[0047] Edge 1 Edge 2 Edge 3 Edge 4 Edge 5 Band 1 Band 2 Band 3 Band 4 Band 5 Original Technology 48 52 39 32 44 52 48 39 45 51 After Improvement 18 12 7 14 17 16 9 11 8 15
[0048] Example 2
[0049] Production line B mainly produces narrow strip steel (large zinc pot), the temperature of the zinc pot is controlled at 455-457℃, and then 5% wt aluminum ingot is added to make the Al content in the zinc pot reach 0.27%, keep the aluminum content unchanged, take liquid from the zinc pot, and remove zinc slag with the liquid taker. Use fluorescence instrument for detection, the Fe content is 0.0064% for the first time and 0.0062% for the second time. Then Al is reduced by 0.01%, and the Fe content of the zinc pot is measured twice at each Al content of the scale. The measurement interval is not less than 24 hours, and the difference of the measured Fe content is less than 0.0003% (unit: wt%, if the condition is not met, repeat the operation until the condition is met), record and calculate the average value, the data is shown in Table 6.
[0050] Table 6
[0051]
[0052]
[0053] Perform image matching and linearization on the data in the table, such as Figure 5 .
[0054] Before the three overhauls, the aluminum content was controlled at 0.20%, 0.22%, and 0.25% respectively before stopping. According to the Fe saturation solubility curve, the Fe content was 0.0113%, 0.0098%, and 0.0078% respectively. Then the zinc pot was cooled to 440℃, the temperature was maintained for 25 hours, and the slag was removed several times. The Fe content in the zinc pot was measured to be 0.0087%, 0.0075%, and 0.0060%. Then the temperature was raised to prepare for the production of outer plates. The production sequence of outer plates was as follows: 1.5mm 60-80 tons, 1.2mm 60-80 tons, 1.0mm 150-200 tons, 0.8mm 200-300 tons, 0.75mm 200-300 tons, 0.7mm 200-300 tons, and the average width was 1200-1300mm. The Fe content in the zinc solution was measured every 4 hours until the saturated Fe content was reached at the corresponding Al content, and the Fe increase rate was calculated, see Table 7.
[0055] Table 7
[0056]
[0057] When the Al content is 0.18%, 0.21%, 0.24%, and 0.27%, the corresponding saturated Fe content N 0 、N 1 、N 2 、N 3 , see Table 8.
[0058] Table 8
[0059] Al content (wt%) 0.18 0.21 0.24 0.26 Saturated Fe content (wt%) <![CDATA[0.0132(N 0 )]]> <![CDATA[0.0101(N 1 )]]> <![CDATA[0.0083(N 2 )]]> <![CDATA[0.0063(N 3 )]]>
[0060] According to the Fe dissolution rate calculated in the above table, the Fe content is calculated from N 1 →N 0 、N 2 →N 1 、N 3 →N 2 Time required x ,t y ,t z Then, according to the formula, the Al reduction rate in the zinc solution required for production is V x 、V y 、V z . See Table 9.
[0061] Table 9
[0062] Al content range (wt%) Time taken (hours) Corresponding rate of aluminum reduction (wt% / hour) 0.18%-0.21% <![CDATA[19.3(t x )]]> <![CDATA[0.0016(V x )]]> 0.21%-0.24% <![CDATA[12.8(t y )]]> <![CDATA[0.0023(V y )]]> 0.24%-0.27% <![CDATA[18.1(t z )]]> <![CDATA[0.0017(V z )]]>
[0063] After the fourth cooling and slag removal of the zinc pot, the Al content of the zinc liquid was detected to be 0.26wt%. First, about 5 tons of zinc liquid were extracted, and then the outer plate was produced in the order of the plan. The thickness specifications were 1.5mm 72 tons, 1.2mm 69 tons, 1.0mm 181 tons, 0.8mm 240 tons, 0.75mm 286 tons, 0.7mm 278 tons, and the average width was 1210mm. Then, pure zinc ingots and zinc ingots with 0.15wt% Al content were added to reduce aluminum. When the Al content in the zinc liquid was between 0.24% and 0.27% (including the left boundary), the aluminum content was reduced according to 0.0017 (V z )wt% / hour, when the AL content of zinc liquid is between 0.21% and 0.24% (including the left boundary), the temperature is adjusted according to 0.0023 (V z )wt% / hour, when the AL content of zinc liquid is between 0.18% and 0.21% (including the left boundary), the temperature is adjusted according to 0.0016 (V z )wt% / hour. The final Al content of zinc liquid is 0.20% and the outer plate production is completed. The production method is used to produce the outer plate zinc slag for automobiles, and the qualified rate is 96.1% in accordance with the "05" grade requirements of the DIN1623-2009 standard, and the number of small black spots is greatly reduced, as shown in Table 10.
[0064] Statistical explanation of the implementation example of small black spots: for the same specification of outer plates, 5 10cm*10cm square samples are taken from the edge and the middle of the strip, and the number of black spots on the front and back sides of the 10 samples is recorded, and the sum of the number of black spots on both sides of a single piece is calculated.
[0065] Table 10
[0066] Edge 1 Edge 2 Edge 3 Edge 4 Edge 5 Band 1 Band 2 Band 3 Band 4 Band 5 Original Technology 37 30 38 42 44 40 36.5 33 39 40 After Improvement 12 14 7 6 8 12 13 11 10 12
[0067] The above is only the basic principle of the present invention, and does not limit the present invention in any way. Any equivalent changes and modifications made to the present invention are within the scope of the patent protection scheme. The technology, shape, and structure described in detail in the present invention are all well-known technologies.
Claims
1. A method for removing slag and accurately controlling slag in the production of continuous hot-dip galvanized automobile outer panels, characterized in that: The Al content of the zinc pot is fixed before overhaul, and the iron content in the zinc pot is saturated. During overhaul, the temperature is lowered to remove slag and after standing still, the Al reduction rate is controlled to produce outer plates.
2. A method for slag removal and precise slag control in the production of continuous hot-dip galvanized automobile outer panels according to claim 1, characterized in that: In addition to cooling and slag removal, the actual temperature of the zinc pot during the entire production measurement and production process is T, unit: ℃, and the target temperature of the zinc pot is T0, unit: ℃, T0-1≤T≤T0+1.
3. A method for slag removal and precise slag control in the production of continuous hot-dip galvanized automobile outer panels according to claim 1, characterized in that: During the production process, the Al content in the zinc pot is increased to 0.26-0.27wt%, and then the composition of the zinc ingot added is controlled to reduce the Al content in the zinc liquid, and the Fe saturation content in the zinc liquid under the corresponding Al content is measured. When the Al content in the zinc pot is reduced to 0.15wt%, the measurement is ended, and the Al and Fe contents in the zinc pot are recorded and the Fe saturation solubility curve is drawn. It is divided into three sections according to the Al content, namely 0.18-0.21wt%, 0.21-0.24wt%, and 0.24-0.27wt%, and the curve is partitioned and linearized according to each section.
4. A method for slag removal and precise slag control in the production of continuous hot-dip galvanized automobile outer panels according to claim 3, characterized in that: During the process of reducing Al in zinc liquid, the Al content is measured with 0.01% as the scale to correspond to the Fe content. The zinc liquid required for measurement does not contain slag particles, ensuring that the composition of the liquid zinc liquid is measured.
5. A method for removing slag and accurately controlling slag in the production of continuous hot-dip galvanized automobile outer panels according to claim 3, characterized in that: The Al content at each scale, the Fe content of the zinc pot is measured twice, the measurement interval is not less than 24 hours, the difference of the measured Fe content is less than 0.0003wt%, if the conditions are not met, repeat the operation until the conditions are met, at which time the Fe content in the zinc liquid reaches saturation, record and calculate the average value of the two measurements.
6. A method for slag removal and precise slag control in the production of continuous hot-dip galvanized automobile outer panels according to claim 3, characterized in that: After the zinc pot is cooled and the slag is removed and left to stand, the time required from the beginning of production until the Fe in the zinc liquid reaches saturation is measured, and the Fe dissolution rate of the strip during the production process is calculated.
7. A method for slag removal and precise slag control in continuous hot-dip galvanized automobile outer panel production according to claim 6, characterized in that: Using three inspections, before stopping, the aluminum content is controlled within a certain value within the three intervals of 0.18-0.21%, 0.21-0.24%, and 0.24-0.27%, excluding the boundaries, and the data X0, X1, and X2 are recorded in wt%. Using the Fe saturation solubility curve, the corresponding saturated Fe content Y0, Y1, and Y2 under the components X0, X1, and X2 are queried in wt%; The zinc pot is cooled to 435-440°C and kept at this temperature for at least 24 hours. During this period, the slag is removed several times. The Fe content in the zinc liquid is measured as M0, M1, and M2 after cooling and removing the slag according to the selected Al content X0, X1, and X2, respectively. The unit is wt%; After starting the machine, arrange the outer plate production, control the Al content in the zinc liquid, and control the addition of zinc ingot components to keep the Al content X0, X1, X2 in the zinc liquid unchanged; after the start of production, measure the iron content in the zinc liquid every 4 hours until the Fe content in the zinc liquid reaches the saturation value Y0, Y1, Y2, and record the time t0, t1, t2.
8. A method for removing slag and accurately controlling slag in the production of continuous hot-dip galvanized automobile outer panels according to claim 7, characterized in that , the rates of dissolved Fe are calculated as V0, V1, and V2, V0 = (Y0-M0) / t0, V1 = (Y1-M1) / t1, and V2 = (Y2-M2) / t2.
9. A method for slag removal and precise slag control in the production of continuous hot-dip galvanized automobile outer panels according to claim 8, characterized in that: By referring to the saturated solubility curve of iron (Fe), the corresponding saturated Fe contents N0, N1, N2, and N3 are accurately found when the Al content is 0.18wt%, 0.21wt%, 0.24wt%, and 0.27wt%, respectively. The zinc liquid is clearly divided into four component points. The difference in Fe content between two adjacent component points is calculated to obtain the absolute values |N1→N0|, |N2→N1|, and |N3→N2|. Combined with the dissolution rate of Fe, the time t required for transition from one component point to the adjacent component point is calculated. x ,t y ,t z , t x =|N1-N0| / V0, t y =|N2-N1| / V1, t z =|N3-N2| / V2; where V0, V1, and V2 represent the Fe dissolution rates at different stages; When the Al content is between 0.18-0.21wt%, 0.21-0.24wt%, and 0.24-0.27wt%, including the left boundary but excluding the right boundary, the Al reduction rate in the zinc liquid during production is V x 、V y 、V z , V x =(0.21%-0.18%) / t x 、V y =(0.24%-0.21%) / t y 、V z =(0.27%-0.24%) / t z .
10. A method for removing slag and accurately controlling slag in the production of continuous hot-dip galvanized automobile outer panels according to claim 9, characterized in that: During the production of outer plates, the zinc ingot component is added to ensure that the Al reduction rate is in accordance with the corresponding aluminum content. x 、V y 、V z The Al and Fe contents in the zinc solution are always kept below the required linearized Fe saturation solubility curve. The smaller the Al content grouping interval is, the closer the linearized curve is to the true value and the more accurate the data is.